Características transversales, diámetro de fibra y resistencia a la tracción de fibra de alpaca según grupos de calidad - Huayra, Daimir (2025)
Alpaca fibre exhibits different quality grades based on fibre diameter and is regulated by the Peruvian Technical Standard – NTP 231.301.2022; however, there are few studies on its cross-sectional characteristics and tensile strength as a function of these different qualities. This study aimed to investigate the cross-sectional characteristics, fibre diameter, and tensile strength in relation to the quality grades. Seven fibre quality groups were established by measuring fibre bundles, and four samples were taken from each group. The cross-sectional characteristics, fibre diameter, and tensile strength were measured using the Fiber Mult, Fiber EC, and Fiber TST devices, respectively. All three variables were affected by fibre quality (p<0.05), showing larger cross-sectional areas and diameters in lower-quality fibres, while tensile strength increased up to quality grade 5 (Fine) before beginning to decrease, possibly due to the higher incidence of medullated fibres and larger medulla area in the lower-quality groups. On the other hand, the tensile strength is higher than that of wool fibres and would not present problems during textile processing. High and positive correlations were obtained between the mean fibre diameter (MFD) and the cross-sectional characteristics, equivalent mean fibre diameter (MFD_e), and apparent mean fibre diameter (MFD_a). The cross-sectional characteristics of alpaca fibre are good estimators of the MFD, but the MFD_e, MFD_a, and cross-sectional characteristics would be the best indicators of fibre fineness.